Stages of Concern, Professional Development, and Levels of Assistive Technology Use in Special Education: Evidence from Jordanian Special Education Teachers - Alqsairi, Munther Mohammad Qasem; Ab Jalil, Habibah (Advances in Social Sciences Research Journal, 2026)
The adoption of assistive technology (AT) in special education holds promise for improving teaching effectiveness and student learning, yet its adoption by teachers remains inconsistent. Guided by the Concerns-Based Adoption Model (CBAM), this study examined the relationship between teachers’ stages of concern, professional development needs, and their levels of AT use (LoU) in public schools in Jordan. A descriptive and correlational quantitative design was employed, with 374 teachers selected through purposive sampling. Data were collected using validated instruments assessing Stages of Concern, professional development needs, and Levels of Use, and analyzed using descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicated that most teachers were in the early stages of AT adoption, with high concerns at Awareness, Informational, and Personal stages, and limited engagement at higher LoU levels such as Integration and Renewal. Both teachers’ concerns and professional development needs were positively associated with LoU, highlighting the importance of addressing personal and professional factors to facilitate effective technology adoption. Findings underscore the need for targeted, sustained professional development, collaborative practices, and adequate institutional support to promote reflective, integrated, and sustainable use of AT in special education. This study contributes to theory by validating CBAM in the context of AT adoption and provides practical guidance for educators and policymakers to enhance teacher readiness, adoption behaviors, and learning outcomes.